Method for removing iron and desulfurizing lithium slag
By combining high-strength magnetic separation and two-stage acid treatment, the problems of low iron and sulfur removal efficiency and high cost in lithium slag are solved, and the efficient and low-cost iron removal and desulfurization effect is achieved, which improves the resource utilization value of lithium slag.
Patent Information
- Application Number
- CN202411800876.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
AI Technical Summary
The existing lithium slag iron removal and desulfurization methods have problems such as poor magnetic separation effect and poor flotation methods on non-sulfide sulfur forms and high cost, making it difficult to effectively remove iron and sulfur from lithium slag.
Using a method of combining two high-strength magnetic separation and two acid treatments, the first magnetic separation and the second magnetic separation perform preliminary removal and further capture of iron, respectively. The two-stage acid treatment uses citric acid and hydrochloric acid, citric acid and nitric acid to completely remove iron and sulfur through acid dissolution, oxidation and complexation.
It significantly improves the removal efficiency of iron and sulfur in lithium slag, reduces treatment costs, complies with the principle of green chemistry, and improves the industrial application value of lithium slag.
Smart Images

Figure CN119588719A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mineral resource processing and utilization, and in particular to a method for removing iron and sulfur from lithium slag. Background Art
[0002] Lithium ore is one of the important sources of lithium. Extracting lithium from ore through various smelting processes is an important way to obtain lithium. Lithium slag is the main by-product generated in the process of extracting lithium by sulfuric acid method. The production of 1 ton of lithium salt will produce about 8-10 tons of lithium slag. Lithium slag contains a large amount of silicon, aluminum and other components, but the residual iron impurities and sulfides exist in various forms, which are difficult to handle, limiting its industrial application value. The accumulation of lithium slag not only causes land waste, but also brings environmental pollution problems. However, lithium slag that has been deironed and desulfurized can replace part of talc for the production of glass fiber. If it can effectively remove iron and desulfurize, and reduce the processing cost at the same time, it will provide important technical support for the resource utilization of lithium slag.
[0003] Patent CN114226413 A discloses a comprehensive treatment process for lithium slag, which includes grinding treatment, first magnetic separation treatment, second magnetic separation treatment, flotation treatment and alkali conversion treatment. It mainly uses magnetic separation treatment to remove iron from lithium slag, but if the lithium slag is mainly composed of non-magnetic iron impurities, the magnetic separation effect will be significantly reduced, resulting in incomplete removal of iron content; flotation method is used to separate sulfides, but the flotation method mainly relies on the hydrophobicity of sulfides (such as pyrite FeS2) for sulfur removal, but it is less effective for sulfate compounds (such as CaSO4, Na2SO4) or other sulfur forms (such as soluble sulfides), and the flotation agent cost is high. Therefore, a lithium slag iron removal and desulfurization treatment method with simple process and low treatment cost is urgently needed. Summary of the invention
[0004] In view of the above-mentioned prior art, the purpose of the present invention is to provide a method for removing iron and desulfurization from lithium slag.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] A first aspect of the present invention provides a method for removing iron and desulfurization from lithium slag, comprising the following steps:
[0007] (1) subjecting the lithium slag to a first magnetic separation treatment, a grinding treatment, and a second magnetic separation treatment in sequence to obtain an iron concentrate and a magnetic separation treatment tailing;
[0008] (2) subjecting the magnetic separation treated tailings to a first-stage acid treatment and a second-stage acid treatment in sequence to obtain a lithium slag for iron removal and desulfurization;
[0009] The acids used in the first-stage acid treatment are citric acid and hydrochloric acid, and the acids used in the second-stage acid treatment are citric acid and nitric acid.
[0010] Preferably, the specific method of one-stage acid treatment is:
[0011] The magnetically treated tailings, citric acid and water are stirred evenly to obtain ore slurry, and then hydrochloric acid with a mass fraction of 36-38% is added, and stirred at 30-60°C for 3-5 hours. After acid dissolution, the precipitate is concentrated and filtered, and dried to obtain a first-stage acid-treated lithium slag product.
[0012] Preferably, the mass ratio of the tailings, citric acid and water for magnetic separation treatment is (40-60): (0.5-1): (40-60); and the amount of hydrochloric acid added is 1%-3% of the weight of the slurry.
[0013] Preferably, the specific method of the second-stage acid treatment is:
[0014] The first-stage acid-treated lithium slag product, citric acid and water are stirred evenly to obtain ore slurry, and then nitric acid with a mass fraction of 65-70% is added, and stirred at 40-80°C for 1-3 hours. After acid dissolution, the precipitate is concentrated and filtered, and dried to obtain a lithium slag product for iron removal and desulfurization.
[0015] Preferably, the mass ratio of the first-stage acid-treated lithium slag product, citric acid and water is (40-60): (0.5-1): (40-60); and the amount of nitric acid added is 1%-3% of the weight of the slurry.
[0016] Preferably, the magnetic field intensity of the first magnetic separation treatment is 8000-12000GS, and the pulp concentration is 20% to 30%.
[0017] Preferably, the grinding treatment method is wet rod grinding, the slurry concentration is adjusted to 40-60%, the grinding fineness is 300 mesh and the pass rate is ≥95%.
[0018] Preferably, the magnetic field intensity of the second magnetic separation treatment is 10000-14000 GS, and the pulp concentration is 40% to 60%.
[0019] Beneficial effects of the present invention:
[0020] 1. The present invention optimizes the removal process of iron and sulfur in lithium slag by combining two high-intensity magnetic separations and two acid treatments, and significantly improves the efficiency of iron removal and desulfurization. The intensity of the first magnetic separation treatment (8000-12000GS) of the present invention is much higher than the low magnetic separation treatment intensity (1000-3000GS) commonly used in the prior art, which significantly enhances the capture ability of weakly magnetic iron minerals (such as hematite, limonite, etc.). After fine grinding, the second magnetic separation treatment is carried out, and the surface area of the iron mineral particles is increased, further improving the capture efficiency of magnetic separation; adding two acid treatments, combining acid dissolution, oxidation and complexation multiple effects, completely remove residual iron minerals and sulfides, and the strong oxidizing property of nitric acid can also effectively dissolve residual iron oxide minerals (such as Fe2O3, FeO(OH)), ensuring that the iron content is further reduced; in the first acid treatment, HCl can effectively dissolve sulfates (such as CaSO4) and part of sulfides (such as FeS) in the lithium slag to generate soluble sulfate ions (SO4 2- ) and release hydrogen sulfide gas (H2S). HCl can also partially dissolve iron compounds and reduce the iron content in lithium slag, laying the foundation for the second-stage acid treatment; the second-stage acid treatment uses 65-70% mass fraction of nitric acid (HNO3). HNO3, as a strong oxidant, can further oxidize and dissolve residual sulfide and iron compounds to generate nitrates and sulfates; citric acid not only plays an important chelating role in the removal of iron, but also has a certain promoting effect on the degradation and removal of sulfur. In the first-stage acid treatment, hydrochloric acid is mainly used to dissolve sulfates. and part of the sulfide, hydrochloric acid provides a large number of hydrogen ions to react with sulfide to generate hydrogen sulfide gas or soluble sulfate, while citric acid complexes iron ions to promote further dissolution of sulfide and prevent iron and sulfur from forming insoluble precipitates. Through synergistic effects, the residual sulfur after the first stage of acid treatment is reduced and the sulfur removal rate is improved. In the second stage of acid treatment, the strong oxidizing property of nitric acid oxidizes the residual sulfide to generate sulfate, and citric acid complexes iron ions to prevent it from forming iron sulfate precipitates with sulfate, ensuring that the sulfate remains in the solution to facilitate the subsequent removal of sulfur.
[0021] 2. The present invention adds citric acid during the acid treatment process. Citric acid is a biodegradable organic acid that does not introduce new pollutants and complies with the principles of green chemistry. Compared with simply relying on strong acids or oxidants to remove sulfur, the addition of citric acid can improve the treatment efficiency and reduce the amount of chemical agents and environmental pollution. During the acid treatment process of lithium slag iron removal and desulfurization, citric acid plays an important role in the degradation and removal of sulfur in the following ways: providing an acidic environment, coordinating with oxidants, and enhancing the dissolution and oxidation rate of sulfides; complexing iron ions to prevent them from forming insoluble precipitation with sulfur and promoting the removal of sulfur; improving the solubility and mobility of sulfur, and possibly forming a soluble complex with certain sulfur-containing compounds to increase the solubility of sulfur. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1: Process flow chart of the lithium slag deironing and desulfurization treatment method of the present invention. DETAILED DESCRIPTION
[0023] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0024] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.
[0025] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.
[0026] The lithium slag obtained by a lithium salt enterprise in Shandong Province from spodumene as raw material through sulfuric acid leaching was treated. The effective components of Fe, C and S in the lithium slag are as follows:
[0027] Table 1 Test results of iron, carbon and sulfur content in lithium slag
[0028]
[0029] Example 1: Lithium slag iron removal and desulfurization method
[0030] (1) First magnetic separation: First, the slurry is adjusted to a slurry concentration of 22.5%, followed by the first magnetic separation with a magnetic field strength of 10,000 GS to obtain iron concentrate and tailings from the first magnetic separation treatment;
[0031] (2) Grinding treatment: The tailings from the first magnetic separation treatment are subjected to wet rod grinding, the pulp concentration is adjusted to 50%, and the grinding fineness is 300 mesh and the passing rate is ≥95%;
[0032] (3) Second magnetic separation: The ground tailings from the first magnetic separation treatment are subjected to a second magnetic separation, with a magnetic field strength of 12000 GS and a pulp concentration adjusted to 50%, to obtain iron concentrate and magnetic separation treatment tailings; the iron concentrate obtained in step (2) and step (3) is collected to obtain a tantalum-niobium rich mixed iron material, providing a suitable raw material for the subsequent comprehensive recovery and utilization of tantalum and niobium;
[0033] (4) One-stage acid treatment: the magnetic separation tailings, citric acid and water are stirred evenly to obtain a slurry, wherein the mass ratio of the magnetic separation tailings, citric acid and water is 49.5:1:49.5, and then 38% hydrochloric acid is added, wherein the amount of hydrochloric acid added is 1% of the weight of the slurry, and the mixture is stirred at 60° C. for 4 hours, and after acid dissolution, the mixture is concentrated, filtered and the precipitate is taken out, and dried to obtain a one-stage acid-treated lithium slag product;
[0034] (5) Second-stage acid treatment: The first-stage acid-treated lithium slag product, citric acid and water are stirred evenly to obtain a slurry, wherein the mass ratio of the first-stage acid-treated lithium slag product, citric acid and water is 49.5:1:49.5, and then nitric acid with a mass fraction of 68% is added, and the amount of nitric acid added is 1% of the weight of the slurry. The mixture is stirred at 60°C for 2 hours, concentrated after acid dissolution, filtered to obtain the precipitate, and dried to obtain a lithium slag product with iron removal and desulfurization.
[0035] Example 2: Lithium slag iron removal and desulfurization method
[0036] (1) First magnetic separation: First, the slurry is adjusted to a slurry concentration of 22.5%, followed by the first magnetic separation with a magnetic field strength of 10,000 GS to obtain iron concentrate and tailings from the first magnetic separation treatment;
[0037] (2) Grinding treatment: The tailings from the first magnetic separation treatment are subjected to wet rod grinding, the pulp concentration is adjusted to 50%, and the grinding fineness is 300 mesh and the passing rate is ≥95%;
[0038] (3) Second magnetic separation: The ground tailings from the first magnetic separation treatment are subjected to a second magnetic separation, with a magnetic field strength of 12000 GS and a pulp concentration adjusted to 50%, to obtain iron concentrate and magnetic separation treatment tailings; the iron concentrate obtained in step (2) and step (3) is collected to obtain a tantalum-niobium rich mixed iron material, providing a suitable raw material for the subsequent comprehensive recovery and utilization of tantalum and niobium;
[0039] (4) One-stage acid treatment: the magnetic separation tailings, citric acid and water are stirred evenly to obtain a slurry, wherein the mass ratio of the magnetic separation tailings, citric acid and water is 49.5:1:49.5, and then 38% hydrochloric acid is added, wherein the amount of hydrochloric acid added is 2% of the weight of the slurry, and the mixture is stirred at 60° C. for 4 hours. After acid dissolution, the mixture is concentrated, filtered and the precipitate is taken out, and dried to obtain a one-stage acid-treated lithium slag product;
[0040] (5) Second-stage acid treatment: The first-stage acid-treated lithium slag product, citric acid and water are stirred evenly to obtain a slurry, wherein the mass ratio of the first-stage acid-treated lithium slag product, citric acid and water is 49.5:1:49.5, and then nitric acid with a mass fraction of 68% is added, and the amount of nitric acid added is 2% of the weight of the slurry. The mixture is stirred at 60°C for 2 hours, concentrated after acid dissolution, filtered to obtain the precipitate, and dried to obtain a lithium slag product with iron removal and desulfurization.
[0041] Example 3: Lithium slag iron removal and desulfurization method
[0042] (1) First magnetic separation: First, the slurry is adjusted to a slurry concentration of 22.5%, followed by the first magnetic separation with a magnetic field strength of 10,000 GS to obtain iron concentrate and tailings from the first magnetic separation treatment;
[0043] (2) Grinding treatment: The tailings from the first magnetic separation treatment are subjected to wet rod grinding, the pulp concentration is adjusted to 50%, and the grinding fineness is 300 mesh and the passing rate is ≥95%;
[0044] (3) Second magnetic separation: The ground tailings from the first magnetic separation treatment are subjected to a second magnetic separation, with a magnetic field strength of 12000 GS and a pulp concentration adjusted to 50%, to obtain iron concentrate and magnetic separation treatment tailings; the iron concentrate obtained in step (2) and step (3) is collected to obtain a tantalum-niobium rich mixed iron material, providing a suitable raw material for the subsequent comprehensive recovery and utilization of tantalum and niobium;
[0045] (4) One-stage acid treatment: the magnetic separation tailings, citric acid and water are stirred evenly to obtain a slurry, wherein the mass ratio of the magnetic separation tailings, citric acid and water is 49.5:1:49.5, and then 38% hydrochloric acid is added, wherein the amount of hydrochloric acid added is 3% of the weight of the slurry, and the mixture is stirred at 60° C. for 4 hours, concentrated after acid dissolution, filtered to obtain a precipitate, and dried to obtain a one-stage acid-treated lithium slag product;
[0046] (5) Second-stage acid treatment: The first-stage acid-treated lithium slag product, citric acid and water are stirred evenly to obtain a slurry, wherein the mass ratio of the first-stage acid-treated lithium slag product, citric acid and water is 49.5:1:49.5, and then nitric acid with a mass fraction of 68% is added, and the amount of nitric acid added is 3% of the weight of the slurry. The mixture is stirred at 60°C for 2 hours, concentrated after acid dissolution, filtered to obtain the precipitate, and dried to obtain a lithium slag product with iron removal and desulfurization.
[0047] Comparative Example 1:
[0048] The difference between this comparative example and Example 2 is:
[0049] The method of one-stage acid treatment is as follows:
[0050] The magnetically treated tailings and water are stirred evenly to obtain a slurry, the mass ratio of the magnetically treated tailings and water is 1:1, and then 38% hydrochloric acid is added, the amount of hydrochloric acid added is 2% of the weight of the slurry, and the mixture is stirred at 60°C for 6 hours. After acid dissolution, the mixture is concentrated, filtered, and the precipitate is dried to obtain a lithium slag product for iron removal and desulfurization.
[0051] Comparative Example 2:
[0052] The difference between this comparative example and Example 2 is:
[0053] The method of one-stage acid treatment is as follows:
[0054] The magnetically treated tailings and water are stirred evenly to obtain a slurry, the mass ratio of the magnetically treated tailings and water is 1:1, and then nitric acid with a mass fraction of 68% is added, and the amount of nitric acid added is 2% of the weight of the slurry. The mixture is stirred at 60°C for 6 hours, concentrated after acid dissolution, filtered to obtain the precipitate, and dried to obtain a lithium slag product for iron removal and desulfurization.
[0055] Comparative Example 3:
[0056] The difference between this comparative example and Example 2 is:
[0057] The method of one-stage acid treatment is as follows:
[0058] The magnetically treated tailings, citric acid and water are stirred evenly to obtain slurry. The mass ratio of the magnetically treated tailings, citric acid and water is 49.5:1:49.5. The slurry is stirred at 60°C for 6 hours. After acid dissolution, the precipitate is concentrated and filtered, and dried to obtain a lithium slag product for iron removal and desulfurization.
[0059] Comparative Example 4:
[0060] The difference between this comparative example and Example 2 is:
[0061] The two-stage acid treatment method is adopted, and the specific method is as follows:
[0062] One-stage acid treatment: the magnetic separation tailings and water are stirred evenly to obtain slurry, the mass ratio of the magnetic separation tailings and water is 1:1, and then 38% hydrochloric acid is added, the amount of hydrochloric acid added is 2.5% of the weight of the slurry, stirred at 60°C for 4 hours, concentrated after acid dissolution, filtered to obtain the precipitate, and dried to obtain a one-stage acid-treated lithium slag product;
[0063] Second stage acid treatment: the first stage acid treated lithium slag product and water are stirred evenly to obtain slurry, the mass ratio of the first stage acid treated lithium slag product and water is 1:1, and then 68% nitric acid by mass is added, the amount of nitric acid added is 4.85% of the weight of the slurry, stirred at 60°C for 2h, concentrated after acid dissolution, filtered to obtain the precipitate, and dried to obtain a lithium slag product for iron removal and desulfurization.
[0064] Comparative Example 5:
[0065] The difference between this comparative example and Example 2 is:
[0066] The two-stage acid treatment method is adopted, and the specific method is as follows:
[0067] One-stage acid treatment: the magnetic separation tailings and water are stirred evenly to obtain slurry, the mass ratio of the magnetic separation tailings and water is 1:1, and then sulfuric acid with a mass fraction of 98% is added, and the amount of sulfuric acid added is 3.0% of the weight of the slurry, and stirred at 60°C for 4 hours. After acid dissolution, the precipitate is concentrated and filtered, and dried to obtain a one-stage acid-treated lithium slag product;
[0068] Second stage acid treatment: the first stage acid treated lithium slag product and water are stirred evenly to obtain slurry, the mass ratio of the first stage acid treated lithium slag product and water is 1:1, and then 68% nitric acid by mass is added, the amount of nitric acid added is 4.85% of the weight of the slurry, stirred at 60°C for 2h, concentrated after acid dissolution, filtered to obtain the precipitate, and dried to obtain a lithium slag product for iron removal and desulfurization.
[0069] Comparative Example 6:
[0070] The difference between this comparative example and Example 2 is:
[0071] The two-stage acid treatment method is adopted, and the specific method is as follows:
[0072] One-stage acid treatment: the magnetic separation tailings and water are stirred evenly to obtain slurry, the mass ratio of the magnetic separation tailings and water is 1:1, and then sulfuric acid with a mass fraction of 98% is added, and the amount of sulfuric acid added is 1.5% of the weight of the slurry, and stirred at 60°C for 4 hours. After acid dissolution, the precipitate is concentrated and filtered, and dried to obtain a one-stage acid-treated lithium slag product;
[0073] Second stage acid treatment: the first stage acid treated lithium slag product and water are stirred evenly to obtain slurry, the mass ratio of the first stage acid treated lithium slag product and water is 1:1, and then 68% nitric acid by mass is added, the amount of nitric acid added is 1.0% of the weight of the slurry, stirred at 60°C for 2h, concentrated after acid dissolution, filtered to obtain the precipitate, and dried to obtain a lithium slag product for iron removal and desulfurization.
[0074] Comparative Example 7:
[0075] The difference between this comparative example and Example 2 is:
[0076] The two-stage acid treatment method is adopted, and the specific method is as follows:
[0077] One-stage acid treatment: the magnetic separation tailings and water are stirred evenly to obtain slurry, the mass ratio of the magnetic separation tailings and water is 1:1, and then sulfuric acid with a mass fraction of 98% is added, and the amount of sulfuric acid added is 1.5% of the weight of the slurry, and stirred at 60°C for 4 hours. After acid dissolution, the precipitate is concentrated and filtered, and dried to obtain a one-stage acid-treated lithium slag product;
[0078] Second stage acid treatment: the first stage acid treated lithium slag product and water are stirred evenly to obtain slurry, the mass ratio of the first stage acid treated lithium slag product and water is 1:1, and then 10% by mass oxalic acid is added, the amount of oxalic acid added is 1.38% by weight of the slurry, stirred at 60°C for 2h, concentrated after acid dissolution, filtered to obtain the precipitate, and dried to obtain a lithium slag product for iron removal and desulfurization.
[0079] Comparative Example 8:
[0080] The difference between this comparative example and Example 2 is:
[0081] The two-stage acid treatment method is adopted, and the specific method is as follows:
[0082] One-stage acid treatment: the magnetic separation tailings and water are stirred evenly to obtain slurry, the mass ratio of the magnetic separation tailings and water is 1:1, and then sulfuric acid with a mass fraction of 98% is added, and the amount of sulfuric acid added is 1.5% of the weight of the slurry, and stirred at 60°C for 4 hours. After acid dissolution, the precipitate is concentrated and filtered, and dried to obtain a one-stage acid-treated lithium slag product;
[0083] Second stage acid treatment: the first stage acid treated lithium slag product and water are stirred evenly to obtain slurry, the mass ratio of the first stage acid treated lithium slag product and water is 1:1, and then 10% by mass oxalic acid is added, and the amount of oxalic acid added is 0.5% by weight of the slurry. After acid dissolution, the precipitate is concentrated and filtered, and dried to obtain a lithium slag product for iron removal and desulfurization.
[0084] Test example:
[0085] The iron and sulfur contents of the lithium slag products for iron removal and desulfurization prepared in Examples 1-3 and Comparative Examples 1-8 were tested, and the results are shown in Table 1.
[0086] Table 2 Test results of iron and sulfur content in lithium slag products after different treatments for iron removal and desulfurization
[0087]
[0088]
[0089] As can be seen from Table 1, by comparing different acid treatment schemes, it is found that the use of 2% hydrochloric acid + citric acid combined with 2% nitric acid + citric acid (Example 2) performs best in the removal effect of iron (Fe) and sulfur (S), with the iron content reduced to 0.03% and the sulfur content reduced to 0.009%. Comparative Examples 1-3 use single acid treatment (such as hydrochloric acid, nitric acid or citric acid) and the effect is obviously poor. While Comparative Examples 4-8 are treated with two different acids respectively, it is found that the selection of other two common acids for compounding cannot achieve the effect of the present application, indicating that the compound of hydrochloric acid, nitric acid and citric acid has a significant synergistic effect. Hydrochloric acid and nitric acid, as strong acids, can effectively dissolve iron and sulfide in lithium slag, while citric acid, as an organic complexing agent, can not only stabilize the dissolved iron and sulfide, prevent it from re-precipitating, but also further improve the efficiency of impurity removal. At the same time, moderate acid concentration can avoid side reactions or impurity residues caused by excessive acid concentration under the premise of ensuring complete reaction.
[0090] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A lithium slag iron removal and desulfurization method, characterized in that: The following steps are involved: (1) subjecting the lithium slag to a first magnetic separation treatment, a grinding treatment, and a second magnetic separation treatment in sequence to obtain an iron concentrate and a magnetic separation treatment tailing; (2) subjecting the magnetic separation treated tailings to a first-stage acid treatment and a second-stage acid treatment in sequence to obtain a lithium slag for iron removal and desulfurization; The acids used in the first-stage acid treatment are citric acid and hydrochloric acid, and the acids used in the second-stage acid treatment are citric acid and nitric acid.
2. The lithium slag iron removal and desulfurization method according to claim 1, characterized in that: The specific method of one-stage acid treatment is: The magnetically treated tailings, citric acid and water are stirred evenly to obtain ore slurry, and then hydrochloric acid with a mass fraction of 36-38% is added, and stirred at 30-60°C for 3-5 hours. After acid dissolution, the precipitate is concentrated and filtered, and dried to obtain a first-stage acid-treated lithium slag product.
3. The lithium slag iron removal and desulfurization method according to claim 2, characterized in that: The mass ratio of the tailings, citric acid and water in magnetic separation treatment is (40-60): (0.5-1): (40-60); the amount of hydrochloric acid added is 1%-3% of the weight of the slurry.
4. The lithium slag iron removal and desulfurization method according to claim 1, characterized in that: The specific method of the second-stage acid treatment is: The first-stage acid-treated lithium slag product, citric acid and water are stirred evenly to obtain ore slurry, and then nitric acid with a mass fraction of 65-70% is added, and stirred at 40-80°C for 1-3 hours. After acid dissolution, the precipitate is concentrated and filtered, and dried to obtain a lithium slag product for iron removal and desulfurization.
5. The lithium slag iron removal and desulfurization method according to claim 4, characterized in that: The mass ratio of the primary acid-treated lithium slag product, citric acid and water is (40-60): (0.5-1): (40-60); the amount of nitric acid added is 1%-3% of the weight of the ore pulp.
6. The lithium slag iron removal and desulfurization method according to claim 1, characterized in that: The magnetic field intensity of the first magnetic separation treatment is 8000-12000GS, and the pulp concentration is 20%-30%.
7. The lithium slag iron removal and desulfurization method according to claim 1, characterized in that: The grinding treatment method is wet rod grinding, the pulp concentration is adjusted to 40-60%, the grinding fineness is 300 mesh and the pass rate is ≥95%.
8. The lithium slag iron removal and desulfurization method according to claim 1, characterized in that: The magnetic field intensity of the second magnetic separation treatment is 10000-14000GS, and the pulp concentration is 40%-60%.
Citation Information
Cited By
Method for removing iron from spodumene smelting slag
CN120608204A